Respuesta :

Answer:

y = 21

x = 74

Step-by-step explanation:

-x + 4y = 10

x - 3y = 11

Let the first eqn be eqn 1 and the second be eqn 2

ie

- x + 4y = 10 --------eqn 1

x - 3y = 11 ----------eqn 2

From eqn 1, make x the subject of the formula

Carrying x over the equal to in order to change the sign from - to +

4y - 10 = x

Substitute the value of x in eqn 2

4y - 10 - 3y = 11

Collecting like terms

4y - 3y = 11 + 10

y = 21

The value of y is 21

Then, substitute the value of y into eqn 1

-x + 4y = 10

-x + 4(21) = 10

-x + 84 = 10

84 -10 = x

In order to get rid of the - sign

x = 74

Therefore,

x = 74

y = 21

Answer:

Step-by-step explanation:

hello : -x + 4y = 10 ....(*)

          x - 3y = 11...(**)

add(*) and(**) : y=21

put this value in(**) : x -3(21) = 11

x= 74